Functioning of active postmenopausal women with osteoporosis - Aline Cristiane Binda; Andersom Ricardo Fréz; Christiane Riedi Daniel; Gladson Ricardo Flor Bertolini; João Afonso Ruaro; Marina Pegoraro Baroni
Abstract Introduction: The multiple aspects of disability in patients with osteoporosis require comprehensive tool for their assessment. The International Classification of Functioning, Disability and Health (ICF) is designed to describe the experience of such patients with theirs functioning. Objective: This study aimed to describe the functioning in a sample of active postmenopausal women with osteoporosis according to the brief ICF core set for osteoporosis. Methods: This cross-sectional study was conducted among active community-dwelling older adults in a southern Brazilian city. Participants were enrolled by convenience sampling from a group conducting supervised aquatic and land-based exercises. Active postmenopausal women with osteoporosis were included. Thirty-two women (mean age 68.0 ± 5.1 years old) participated in the evaluation. The brief ICF core set for osteoporosis was used to establish functional profiles. The categories were considered valid when ≥20% of participants showed some disability (according to ICF qualifiers). Results: No category showed a high level of disability, as >50% of women rated by qualifiers .3 or .4. Only the category e580 was considered by all participants as a facilitator. Conclusion: The brief ICF core set for osteoporosis results demonstrated that this classification system is representative to describe the functional profile of the sample. Active postmenopausal women with osteoporosis presented few impairments related to body functions and structures, activities and participation and environmental factors.